Genetic and metabolic engineering approaches for enhanced biodesulfurization of petroleum fractions - Bagchi, Asheemita; Srivastava, Preeti (Frontiers in Bioengineering and Biotechnology, 2024)
Sulfur, an abundant component in crude oil, has been known to cause severe damage to the environment, human health and poison the catalysts used in combustion engines. Hydrodesulfurization, the conventionally used method, is not sufficient to remove the thiophenes like Dibenzothiophene (DBT) and other aromatic heterocyclics. The push for "ultra-clean" fuels, with sulfur content less than 15ppm drives the need for deep desulfurization. Thus, in conjunction with hydrodesulfurization, efficient, and eco-friendly ways of deep desulfurization, like biodesulfurization will be desirable. In biodesulfurization naturally desulfurizing microorganisms are used, with genetic engineering and biotechnology, to remove the sulfur content of crude oil below 15ppm. In this review, we describe genetic engineering and metabolic engineering approaches reported to date to develop more efficient ways to carry out biodesulfurization to make it a practically applicable reality.